Masdevallia leonor-baeziana (Pleurothallidinae) : a new species from the Andean-Amazonian foothills of Caquetá, Colombia - Perdomo, Oscar
We describe and illustrate a new species of Masdevallia from the Andean-Amazonian foothills of Caquetá, Colombia. Masdevallia leonor-baeziana belongs to Masdevallia subsect. Saltatrices,within the M. constricta group. It is most similar to M. constricta, but it can be distinguished by the shorter sepals and sepaline tails that do not surpass the tube length, and the shorter, sigmoid-ovate lip. We proposed categorizing the species as Critically Endangered (CR) based on the B and D IUCN red list criteria.